Stabilising determinants in the transmission of phonotactic systems: Diachrony and acquisition of coda clusters in Dutch and Afrikaans - Baumann, Andreas; Wissing, Daan (Stellenbosch Papers in Linguistics Plus, 2018)
The phonotactic system of Afrikaans underwent multiple changes in its diachronic development. While some consonant clusters got lost, others still surface in contemporary Afrikaans. In this paper, we investigate to what extent articulatory difference between the segments of a cluster contribute to its successful transmission. We proceed in two steps. First, we analyse the respective effects of differences in manner of articulation, place of articulation and voicing on the age at which a cluster is acquired by analysing Dutch acquisition data. Second, we investigate the role that these articulatory differences play in the diachronic frequency development from Dutch to Afrikaans. We demonstrate that large differences in manner of articulation between segments contribute to a cluster’s success in acquisition and diachrony. In contrast, large differences in place of articulation have impeding effects, while voicing difference shows a more complicated behaviour.